Self-Regulatory Learning Patterns of Disabled Students at UIN Sunan Kalijaga Yogyakarta - Zamakhsari Zamakhsari; Siswanto Masruri; Sutrisno Sutrisno (Universitas Muhammadiyah Yogyakarta, 2020)
This study aims to find the learning patterns of students with visual disabilities through self-regulation. This research approach is qualitative with phenomenological design and descriptive methods. This research study is a self-regulation pattern in students with visual disabilities by observing the interaction between students and the learning environment and social environments to achieve individual and academic goals. The author collected the data through interviews, observations, and documentation. This study concludes that this informants' metacognitive contribution provided positive and supportive directions for learning patterns based on students' self-regulation with visual disabilities UIN Sunan Kalijaga Yogyakarta. The self-regulation of informants in learning formed from this metacognitive knowledge relied on the sense of hearing. The strategy came from listening, taking, and reading notes.